Implementation of transformational leadership in increasing the organizational commitment of civil servants - Hartono, Hartono; Salju, Salju; Qamaruddin, Muh Yusuf (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Leaders have an important role in an organization. Various tasks are the responsibility of the leader in an organization, including increasing the organizational commitment of civil servants at the Andi Jemma Airport Operator Unit Office. This can also be influenced by the leadership style used by a leader, one of the leadership styles that can affect the organizational commitment of civil servants is transformational leadership. The purpose of this study is to explore the implementation of transformational leadership in improving the organizational commitment of civil servants at the Andi Jemma Airport Operator Unit Office. This research uses exploratory research with a qualitative approach. Primary data sources in this study are the results of questionnaires and secondary data sources from the exploration of various journals. Activities in data analysis are data reduction, data presentation, and conclusion drawing or verification. The research results show that to achieve optimal results and maintain organizational sustainability, the role of human resource (HR) quality is key, which affects organizational performance and success. Transformational leadership style, with aspects of employee empowerment, effective communication, and individual development, emerges as an approach that has the potential to increase employee organizational commitment. The implementation of transformational leadership can form an environment that motivates and inspires employees to be dedicated to the organization, positively impacting the performance and existence of the organization, as in the case of Andi Jemma Airport.